An essay of visual anthropology on daily life of workers during the COVID-19 pandemic in Cascavel – PR, Brazil (Research, Society and Development, 2021)
This essay on Visual Anthropology aims to narrate, imagetically, through a photoetnography, the daily life of workers, in their multiple experiences that, due to the social conditions or the profession they exercise, are unable to comply with the social distance recommendations during the COVID-19 pandemic, in the city of Cascavel-PR, Brazil. The article is structured in two parts. In the first, formed by a written text, we resort to the concept of apartheid, as a perspective of analysis to show its effects in the daily lives of workers; thus, we briefly present the field of Visual Anthropology and photoetnography. Finally, we discuss our research field, marked by profound evidence of vulnerability and social injustice. In the second part, essentially formed by an imagetic language, we present the daily life of the natives. With this organization, resorting to textual and imagery languages, we offer the reader two input possibilities to cycle through multiple corridors of interpretations, being possible to choose between starting reading through images or through textual writing.